Comparative Evaluation of Micro Tensile Bond Strength and Microleakage of Ionoseal Glass-Composite as a Fissure Sealant Material, Following Four Different Enamel Surface Pretreatments - Samaneh Hesami; Davood Ghasemi; Shahriar Shahriari (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Sealants are placed to prevent carious lesion initiation and to arrest caries progression by providing a physical barrier that inhibits microorganisms and food particles from collecting in pit and fissures .The two most common materials used for sealing pits and fissures are resins and glass-ionomers. Ionoseal is a light curing GI composite cement.The aim of this study was to compare the microtensile bond strength and microleakage of Ionoseal with different surface pretreatment.Materials and Methods:This in vitro ,an experimental study was conducted on 95 sound human premolar in 5 groups(in each group 5 teeth for microtensile test and 14 teeth for microleakage test).A :35% phosphoric acid + total etch adhesive + Ionoseal ,B :universal adhesive + Ionoseal ,C: 35% phosphoric acid + Ionoseal,D: Ionoseal, E: 35% phosphoric acid + Embrace fissure sealant. On the prepared buccal enamel of each tooth, a 5 mm block of the sealing material was created and underwent thermocycling .By serially cutting, specimens about1×1mm in cross section were obtained and loaded in tensile (0.5 mm/min) until failure occurred .For microleakage test,sealing material was placed into the prepared occlusal fissures and teeth were thermocycled and then immersed in methylene blue 5% .An incision was made buccolingually. The dye penetration rate was measured based on Williams and winter criteria under stereomicroscope.Results: Mean microtensile bond strength was significantly different between groups (P